The German Journal of Veterinary Research- A Platform for veterinary medicine and One-Health - Heinrich Neubauer; Hafez Hafez (German Journal of Veterinary Research)
Animal health is the fundamental pre-requisite to secure global food safety and public health. Infectious animal diseases distress societies and damage international trade, and they continue to emerge and re-emerge. Research in veterinary science traditionally focuses on epidemiology, diagnosis, treatment, prevention, control, vaccine development and animal welfare. A better understanding of animal disease\'s nature will improve livestock health and productivity and contribute to the various efforts to foster human health. Thus, collaborative research across countries, agencies, and institutions should be supported by generous funds, a liberal legal framework, and disseminating research results globally